The Memory Thief - Anderson, Jodi Lynn (Simon & Schuster Children's Publishing, 2021)
Intro – Title Page – Dedication – Prologue – Part 1 – Chapter 1 – Chapter 2 – Chapter 3 – Chapter 4 – Chapter 5 – Chapter 6 – Chapter 7 – Chapter 8 – Chapter 9 – Chapter 10 – Chapter 11 – Part 2 – Chapter 12 – Chapter 13 – Chapter 14 – Chapter 15 – Chapter 16 – Chapter 17 – Chapter 18 – Chapter 19 – Chapter 20 – Chapter 21 – Chapter 22 – Chapter 23 – Chapter 24 – Chapter 25 – Chapter 26 – Chapter 27 – Chapter 28 – Chapter 29 – Chapter 30 – Part 3 – Chapter 31 – Chapter 32 – Acknowledgments – About the Author – Copyright.
Description based on publisher supplied metadata and other sources
Keywords: Witches; Magic; Mothers and daughters; Witches-Juvenile fiction; Magic-Juvenile fiction; Mothers and daughters-Juvenile fiction; Electronic books